Abscisic acid positively regulates rice spikelet closure - Youming Huang; Qiusheng Xiao; Huilan Zeng; Xiaochun Zeng (PLoS ONE, 2026)
To investigate the mechanisms underlying rice glume closure and develop effective regulatory strategies, we examined both fertile (Xingan Zaozhan, Jiazao 70, and Zhenshan 97B) and sterile (Qiyuan S, Yue 4A, and Zhenshan 97A) varieties. ABA and fluridone (FL) were applied to mature panicles at various concentrations to assess closure rates, duration, and endogenous ABA levels in spikelets. RNA sequencing of lodicules was performed to analyze differential expression of genes involved in ABA synthesis and signal transduction during opening and closing phases. Additionally, methyl jasmonate (MeJA) combined with ABA (MeJA + ABA) was applied to female parents in hybrid breeding to evaluate seed setting rate, spikelet cracking rate, and yield increase. ABA treatment significantly accelerated spikelet closure, reduced closure duration, and increased final closure rates in both fertile and sterile lines, with optimal concentrations of 200–400 mg/L. In contrast, FL treatment delayed closure, prolonged the opening-closing duration, and decreased final closure rates. Endogenous ABA levels in palea and lemma were significantly lower during initial opening and closing stages compared to the maximum opening angle. During the Ory-15 min vs. Ory-40 min transition, genes encoding 9-cis-epoxycarotenoid dioxygenase (NCED) and abscisic aldehyde oxidase (AAO) were significantly up-regulated, along with PYR/PYL, SnRK2, and ABF family genes, while PP2C family genes were down-regulated. The combined MeJA + ABA treatment significantly improved glume closure rates and hybrid seed yield. These results demonstrate that ABA promotes rice spikelet closure while FL inhibits it, highlighting ABA’s crucial role in hybrid breeding. The MeJA + ABA combination offers a promising strategy to enhance hybrid seed yield and quality.